Public expenditure on education and its impact on child labor in Cajamarca and Huancavelica - Acuña Ramírez, Jesús Alexander (2021)
Objective: Determine the impact of public spending on education on child labor in Cajamarca and Huancavelica, 2012-2020 period. Method: The research was of a quantitative, non-experimental and cross-sectional type; with an explanatory scope; the population was based on the data from the statistical series of public spending on education for both primary and secondary education along with the rate of boys, girls and teenagers in the departments of Cajamarca and Huancavelica, which were obtained from the National Institute of Statistics and Informatics and the platform of Educational Quality Statistics (Peru’s Ministry of Education). Results: The impact of total spending on education in soles per student is less than 0,0078%; being clear when the economic theory of education coincides with the statistical and econometric evidence found with the fixed effects method. It is evidenced that Huancavelica has adverse conditions to the economic well-being, since it has its own characteristics that increase the level of child labor, unlike Cajamarca. Conclusion: Public spending on education for both primary and secondary levels have a negative impact on child labor.